Educational Processes for Volcanic Risk Management (Vrm) at an Educational Institution (Ei) in The Department of Nariño (COLOMBIA) (2020)
Objective: to analyze the educational processes in Volcanic Risk Management (VRM) of the project of Education in Emergencies (EiE) at the Institución Educativa San Bartolomé (IESBA) in the Municipality of La Florida in the Department of Nariño (Colombia). Method: it is a qualitative study oriented from the historical-hermeneutical paradigm including ethnographic elements. Its participants were students, teachers and administrative staff of the IESBA. The techniques and instruments for collecting information included participant observation, individual and group semi-structured interviews, personal communications and document review. The constant comparison method was used for information analysis. Results: the interaction and the communication in the educational institution, as well as the community participation lead to the adoption and the strengthening of the knowledge referred to the VRM, from the different teaching strategies that involve not only the educational community, but also the community in general. Conclusions: the work done by the IESBA is consistent with the needs and demands of the context in which it is set, highlighting from the EiE project, elements such as community participation and institutional and inter-institutional work. This study shows a strategy that can be replicated in diverse EI that are highly exposed to the volcanic risk. Finally, considering inclusive education is also an indicator of improvement.